All good things require effort: the U-shaped relationship between information technology resources and firm performance - Choi, Hyeri; Park, Min Jae (Technology Analysis and Strategic Management, 2024)
This study attempts to understand the processes that occur until the adoption of information technology resources yields the expected results. In particular, a value chain perspective is integrated with this relationship to investigate how the characteristics of each business activity result in distinct outcomes, thereby providing specific evidence for the management of information technology resources. The study also examines the moderating role of organisational restructuring in the relationship between information technology resources and firm performance. This study takes a third way to look at this relationship, assuming that both impacts can be observed, depending on the usage level. By doing so, this study may provide some clues for the mechanisms behind assimilating technology into organisations.
Keywords: ICT; information technology resources; organisational restructuring; SMEs; U-shaped relationship